Molecular hydrogen: a sustainable strategy for agricultural and food production challenges - Alwazeer, Duried; Hancock, John T.; Russell, Grace; Stratakos, Alexandros Ch.; Li, Longna; Çiğdem, Ayhan; Engin, Tunahan; LeBaron, Tyler W. (Frontiers in Food Science and Technology, 2024)
The world is confronting numerous challenges, including global warming, health epidemics, and population growth, each presenting significant threats to the stability and sustainability of our planet's ecosystems. Such issues have collectively contributed to a reduction in agricultural productivity, corresponding with an increase in demand and costs of essential commodities. This critical situation requires more sustainable environmental, social, and technological solutions. Molecular hydrogen (H2) has been suggested as a "green" solution for our energy needs and many health, agricultural, and food applications. H2 supplementation in agriculture may represent a novel and low-carbon biotechnological strategy applicable to the abundant production of crops, vegetables, and fruits in agri-food chains. H2 is a potential green alternative to conventional chemical fertilizers. The use of a hydrogen-rich water irrigation system may also provide other health-related advantages, i.e., decreasing the heavy metal accumulation in crops. By adopting a H₂ strategy, crop producers, food processors, and decision-makers can contribute to sustainable solutions in the face of global challenges such as climate change, communicable disease epidemics, and a growing population. The versatile applications of H₂ in agriculture and the wider food industry position it as a uniquely suitable approach to address today's significant challenges, potentially fostering better crop production and positively impacting the agri-food chain. The present review is timely in combining the latest knowledge about the potential applications of H₂ in the agriculture and food industry, from farm to fork.